Introduction to homeland security principles of all-hazards response - Bullock, Jane A. (Butterworth-Heinemann homeland security series., 2009)
Bullock and Haddow have set the standard for homeland security textbooks, and they follow up their top-selling second edition with this substantially improved third edition. Faculty, students, and professional practitioners value the decades of experience that the authors bring to their analysis, and their passionate argument for an all-hazards approach to enhancing America's safety is now presented still more cogently. Links to the most current online government information help to keep the text up to date in this rapidly developing field. The pedagogical elements in the bound book as well as.